The Learning Media Application "BELIPARU" Oriented Towards the Mastery of Fifth-Grade Students' Concepts of the Water Cycle Material - Fanny Destiani; Atep Sujana; Ani Nur Aeni (Mimbar Ilmu, 2023)
The low level of mastery of concepts by elementary school students in Indonesia, especially in science subjects, impacts students' low learning outcomes and enthusiasm for participating in teaching and learning activities. So to maximize the learning process, teachers must start utilizing the use of media. This study aims to see the effectiveness of the "BELIPARU" application media, which is oriented towards mastering the concept of fifth-grade students. This research belongs to the type of development research developed using the Borg and Gall model, with four research stages consisting of the idea gathering and reference stages, product manufacturing stage, media validation stage and material validation stage, product revision stage, and trial stage. The test subjects were conducted on 29 students in class V. This data collection method was carried out through observation, written test instruments in the form of pretest and post-test questions, and closed questionnaires for students. The data obtained in this study were then analyzed using descriptive-quantitative analysis techniques through the SPSS application, which were then thoroughly described using descriptions. The research analysis showed that the media expert test produced a percentage of 92.5% in the very good category. In comparison, the results of the material experts produced a percentage of 90.6% in the very good category, although there was a slight minor revision in the validator. Furthermore, the results of the pretest activity trials showed an average of 22.24, and the results of post-test activity testing showed an average of 64.31. Based on these results, Android-based applications are very suitable for students' learning process, especially in increasing mastery of concepts.